Психологические тенденции проявления настроя как готовности студентов к успешной работе - Романовский, Александр Георгиевич (НТУ "ХПИ", 2012)
The article discusses current trends in the psychological manifestations of the mental state of readiness as the mood of students for success.Understanding these trends in scientific and pedagogical staff of the university allows you to more specifically analyze their methodological possibilities for the development and maintenance of this phenomenon have trained as a perfectly formed professionals.
Keywords: прогресс; возможности; настрой; опыт